Changing generic strategies: Likelihood, direction, and performance implications - Zajac, Edward J.; Shortell, Stephen M. (Strategic Management Journal, 1989)
Abstract This study argues for greater research attention to the issue of changing generic strategies over time. The study proposes two sources of theoretical tension relating to changing strategies: (1) the notion of equally viable generic strategies versus particularly appropriate strategy/environment combinations, and (2) the relative influence of process (ability to change strategies) versus content (desire to change strategies) issues. Questions relating to these tensions are then examined empirically in an industry‐specific analysis of the likelihood, direction, and performance implications of an organization'S changing its strategy in response to an environmental shift. The findings suggest that changes in generic strategy are not rare, and that organizations do not perceive generic strategies to be equally viable in different environments across time. Performance differences were also found across generic strategies, but not between firms that changed their strategy versus those that did not.